Blue fluorescence of cyano-tryptophan predicts local electrostatics and hydrogen bonding in biomolecules - Haldar, Tapas; Chatterjee, Srijan; Alam, Md Nirshad; Maity, Pradip; Bagchi, Sayan (Journal of Physical Chemistry B, 2022)
Cyano-tryptophan is an unnatural fluorescent amino acid that emits in the visible region. Along with the structural similarity with tryptophan, the unique photophysical properties of this fluorophore make it an ideal probe for biophysical research. Herein, combining fluorescence spectroscopy, infrared spectroscopy, and molecular dynamics simulations, we show that the cyano-tryptophan's emission energy quantifies the underlying bond-specific noncovalent interactions in terms of the electric field. We further report the use of fluorophore's emission energy to predict its hydrogen bond characteristics. We demonstrate that combining experiments with molecular dynamics simulations can provide the hydrogen bonding status of the nitrile moiety. In addition, we report a method to differentiate between aqueous and nonaqueous hydrogen-bonding partners. Using a phenomenological approach, we demonstrate that the presence of the cyano-indole moiety is responsible for the distinct correlations between the fluorophore's emission and the electrostatic forces on the nitrile bond. As indole is a privileged scaffold for both native amino acids and nucleobases, cyano-indoles will have many multifaceted applications.